The impact of reforms and neoliberal policies on gender equity in Uzbekistan’s higher education - Kasimov, Otabek; Farkas, Beáta (Society Register, 2025)
This study investigates the impact of Uzbekistan’s reforms and neoliberal policies since 2017, particularly on gender equity in higher education institutions (HEIs). Through semi-structured interviews with 32 key stakeholders, the research highlights increased female enrolment and participation, with notable growth in female doctoral students, mainly due to government interventions like quotas and financial support. However, persistent challenges such as gender biases, work-life balance issues, and underrepresentation in leadership continue to affect women’s academic careers. Despite policy advancements, structural inequalities remain, limiting women’s opportunities for professional growth. This research contributes to understanding the intersection of gender and neoliberal reforms in Uzbekistan’s higher education landscape. It emphasizes the need for further policy and cultural shifts to address ongoing gender disparities.